THE ROLE OF LANGUAGE IN ADVERTISEMENT - Widyahening, Dr. Ch. Evy Tri (PROCEEDING INTERNASIONAL SEMINAR, 2015)
Advertisement becomes an important part in humanâs life. It has formed culture maker in society. Advertisement becomes one of crucial things that should be done. It has a power to persuade consumerâs desire to the product in society through image ideology association. Advertisement build image ideology of product then it also uses sign systems or language which has relationship with moral values. One of ideology which can be called sign system or ad language is gender ideology, especially is about women exploitation as a sign system. It can be said that many advertisement has used many words which has negative meanings, sensitive meanings, porn meanings, etc and all of them points to the woman exploitation, because many advertisements usually use women to be a target of a product and also to be an agent of change. So, in interpreting sign system or language, advertisement has multidimensional meaning not only to market a product but also to interpret sign system or language. Then, language system has a power because there is an ideology which always hide in it. Ideology is inherent within language, it means that there is higher significant relevance when the context is placed in the frame of modernity which is called the third wave. The power of language has affected dan hidden in advertisement then it has become social infrastructure which has a total power. This power of language can effect persception, attitude, behaviour, and point of view of society.Keywords: the power of language, advertisement, and sign system